Membangun Orientasi Pelangggan Secara Profesional dengan Dasar Etika Bisnis - Asyari Asyari; Dipateruna Dipateruna; Rose Rosaria Z (Ekonomis: Journal of Economics and Business, 2022)
This study aims to examine the effect of business ethics and professional competence as independent variables with customer satisfaction as the independent variable. The type of research used is descriptive quantitative with a sample of 90 employees at the company PT. Pharos and Bio Farma. The data analysis technique used hypothesis testing with multiple linear regression. The results of the study partially illustrate that the t-test of business ethics variables has a significant effect on customer satisfaction and professional competence also has an effect on customer satisfaction. based on the simultaneous F-test and R-test produced simultaneously, business ethics and professional competence have an effect on customer satisfaction. and based on the R test, the two variables of business ethics and professional competence were able to give an effect of 54.9 percent on customer satisfaction.